AID‐expressing epithelium is protected from oncogenic transformation by an NKG2D surveillance pathway - Arantxa Pérez‐García; Pablo Pérez‐Durán; Thomas Wossning; Isora V Sernandez; Sonia M Mur; Marta Cañamero; Francisco X Real; Almudena R Ramiro (EMBO Molecular Medicine)
Abstract Activation‐induced deaminase (AID) initiates secondary antibody diversification in germinal center B cells, giving rise to higher affinity antibodies through somatic hypermutation (SHM) or to isotype‐switched antibodies through class switch recombination (CSR). SHM and CSR are triggered by AID‐mediated deamination of cytosines in immunoglobulin genes. Importantly, AID activity in B cells is not restricted to Ig loci and can promote mutations and pro‐lymphomagenic translocations, establishing a direct oncogenic mechanism for germinal center‐derived neoplasias. AID is also expressed in response to inflammatory cues in epithelial cells, raising the possibility that AID mutagenic activity might drive carcinoma development. We directly tested this hypothesis by generating conditional knock‐in mouse models for AID overexpression in colon and pancreas epithelium. AID overexpression alone was not sufficient to promote epithelial cell neoplasia in these tissues, in spite of displaying mutagenic and genotoxic activity. Instead, we found that heterologous AID expression in pancreas promotes the expression of NKG2D ligands, the recruitment of CD8+ T cells, and the induction of epithelial cell death. Our results indicate that AID oncogenic potential in epithelial cells can be neutralized by immunosurveillance protective mechanisms.